Botaiho : Japanese organised crime under the Boryokudan countermeasures law - Hill, Peter B. E. (2000)
This thesis is an investigation into the effects of the 1992 böryokudan countermeasures law (böryokudan taisaku ha or, more simply, bötaihö) on Japan's organised crime syndicates (böryokudan or yakuza). Underlying this examination is a functionalist perspective of organised crime which rests on the premise that, far from being unambiguously socially dysfunctional, organised crime groups exist because they satisfy needs held by various sections of society (both in the upper and underworlds). This approach demystifies many of the supposedly unique aspects of the böryokudan/yakuza (such as yakuza-authority symbiosis) and places Japan within the compass of modem organised-crime studies. An empirical overview of the böryokudan's development from 1945 to 1992 shows that the prime dynamic behind this evolution has been the legal and law-enforcement environment within which these groups exist and that frequently the impact of these changes has been socially undesirable. Attempts to examine whether or not the bötaihö has similarly exacerbated organised criminality in Japan are hampered by the collapse of Japan's bubble economy in 1990. This event had profound consequences for boryokudan groups rendering many activities unviable, whilst simultaneously creating new opportunities. Despite these extraneous considerations, the bötaihö has had an observable impact on many aspects of the böryokudan's activities and some of these consequences have been socially undesirable. The legal analysis of the bötaihö is placed in the wider context of international organised-crime control measures, in particular America's RICO statutes and European laws, both of which were highly influential in the debate within Japan concerning the framing of new anti-böryokudan laws. The thesis concludes by arguing that the radically different structure of the bötaihö, vis-ä-vis these alternative models, is part of a wider reversion to pre-war legal and policing norms in which, in addition to enforcement of the criminal law, the police also exercise considerable administrative powers